Diagnosis of Blood and Bone Marrow Disorders (Springer International Publishing, 2018)
This book focuses on hematopoietic and lymphoid neoplasms that initially present as peripheral blood abnormalities, with either cytopenias or elevated peripheral blood counts, as well as non-neoplastic conditions that may raise concern for a hematologic malignancy. The scope of the book includes myelodysplastic syndromes (MDS), myeloproliferative neoplasms (MPN), mixed myelodysplastic/myeloproliferative neoplasms (MDS/MPN), as well as lymphomas and lymphoid leukemias that typically present initially with peripheral blood abnormalities. Within each category, a comprehensive list of differential diagnoses is discussed. For each disease entity, the reader is updated with new molecular genetic data, biomarkers, and recent applications of immunophenotyping, and how to incorporate the new information in disease diagnosis and classifications is illustrated, including the use of diagnostic algorithms where appropriate. The book employs the revised WHO Classification of Hematopoietic Neoplasms for all disease entities. Diagnosis of Blood and Bone Marrow Disorders will serve as a very useful resource for pathologists, pathologists in training, hematologists and medical technologists who are involved in the clinical work-up of patients with bone marrow and blood neoplasms. It will provide a practical and concise yet comprehensive review.